Obesity, Cardiovascular Fitness, and Inhibition Function: An Electrophysiological Study - Song, Tai-Fen; Chi, Lin; Chu, Chien-Heng; Chen, Feng-Tzu; Zhou, Chenglin; Chang, Yu-Kai (Frontiers in Psychology, 2016)
The purpose of the present study was to examine how obesity and cardiovascular fitness are associated with the inhibition aspect of executive function from behavioral and electrophysiological perspectives. One hundred college students, aged 18 to 25 years, were categorized into four groups of equal size on the basis of body mass index and cardiovascular fitness: a normal-weight and high-fitness (NH) group, an obese-weight and high-fitness (OH) group, a normal-weight and low-fitness (NL) group, and an obese-weight and low-fitness (OL) group. Behavioral measures of response time and number of errors, as well as event-related potential (ERP) measures of P3 and N1, were assessed during the Stroop Task. The results revealed that, in general, the NH group exhibited shorter response times and larger P3 amplitudes relative to the OH, NL, and OL groups, wherein the OL group exhibited the longest response time in the incongruent condition. No group differences in N1 indices were also revealed. These findings suggest that the status of being both normal weight and having high cardiovascular fitness is associated with better behavioral and later stages of electrophysiological indices of inhibition. However, these benefits in inhibition function would be lost in an individual who is obese or has low cardiovascular fitness, reflecting the importance keeping both normal weight and having high cardiovascular fitness.